MEASUREMENT AND INTERPRETATION OF MIXED MERCAPTOETHYL PALMATE AND SODIUM SULFIDE VISCOSITY DATA - Anggika Mahdyani, Hasna
In process industries such as the food industry, viscosity values are considered as they can affect the characteristics of process equipment. Viscosity data is also needed in designing and evaluating work, such as stirring operations in reactors. Up until now, there has been no definitive viscosity data for the mixed system of MEP (Merkaptoetil Palmat) and Na2S (Sodium Sulfide). The MEP and Na2S system was discovered in the synthesis of palm-based PVC thermal stabilizer. Thermal stabilizer is essential for PVC to prevent thermal degradation. Viscosity measurements were measured using a digital Brookfield viscometer type DV-E with RV spindle number 5. The study was conducted with two samples of MEP and Na2S mixtures with variations in Na2S concentration of 5% and 10%. Measurements were made for each sample with a spindle speed variation of 1 – 100 rpm at a temperature variation of 30oC – 60oC. The Power Law model was used due to the highest R2 value among the other model equations, making it very suitable for the MEP and Na2S system. The relationship between viscosity and shear rate as well as shear stress and shear rate is non-linear hence considered as pseudoplastic non-Newtonian fluid with shear thinning behavior. Apparent viscosity (?) of MEP and Na2S mixed fluid with 5% Na2S concentration at a temperature variation of 30 – 60oC is in the range of 1120 - 165,710 cP and at 10% Na2S concentration with the same temperature variation, the apparent viscosity value is in the range of 2750 – 173,170 cP. The optimum temperature of the mixture for the stirring and agitation process in the reactor is 60oC.